Giustizia sociale: eguaglianza, diseguaglianza, rispetto - Giovanola, Benedetta (Filosofia Morale/Moral Philosophy, 2023)
The article analyzes the relationship between equality and inequality in contemporary theories of justice and, emphasizing some often overlooked aspects of Rawls’s account, argues the complementarity of the distributive dimension and the socio-relational dimension of social justice, moving from an analysis of respect, understood as respect for persons both as persons and as particular individuals. The article also shows that, starting from this twofold understanding of respect, it is possible to clarify the ethical-normative dimension of social justice and recover the most proper sense of the good of justice, which consists in the promotion both of fair distribution and relations of equality, and of practices and bonds of civic friendship and social solidarity.